2013
DOI: 10.1159/000346639
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Discharge: Role of Ductoscopy in Comparison with Standard Diagnostic Tests

Abstract: Background: This study aims to assess the role of ductoscopy for detecting intraductal anomalies in patients with nipple discharge in comparison to conventional tests and to find an effective combination of both approaches. Materials and Methods: Prior to duct excision, ductoscopy was performed in 97 women. Histologic and all other diagnostic results were compared. Sensitivity, specificity, and efficiency were calculated for all methods. These parameters were also calculated for all possible test combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
1
17
3
1
Order By: Relevance
“…The literature reports sensitivities ranging from 60 to 77% corresponding with specificities between 25 and 66.7% [10,23,25]. Differences between our results and those reported in previous studies can be explained by variations in image interpretation.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The literature reports sensitivities ranging from 60 to 77% corresponding with specificities between 25 and 66.7% [10,23,25]. Differences between our results and those reported in previous studies can be explained by variations in image interpretation.…”
Section: Discussioncontrasting
confidence: 77%
“…In their study on 71 patients, Grunwald et al [10] reported a sensitivity of 37.9% and a specificity of 92.3%. In their retrospective study, Albrecht et al [23] calculated a sensitivity of 9% and a specificity of 100%, explaining the low sensitivity with a large number of false-negative results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Показания к ЭМДС чаще всего возникают при наличии патологических выделений из сосков, хотя имеются единичные публикации о применении эн-доскопии и в случаях кист МЖ [17,23].…”
unclassified